From From ideology to inequality: Examining the socialist effect on South Africa's pandemic politics - Demi Harmse (Journal of BRICS Studies)
The BRICS grouping represents an inter-state association of five major emerging national economies whose political influence is mobilized to encourage economic development and inclusivity. However, without an internalized commitment to domestic socio-economic vulnerabilities, the platform lacks the legitimacy needed to compel buy-in from a larger audience. It is a fruitless endeavor to labor under the assumption that socio-economic inequality is abnormal. Even so, there is an amicable, yet unrealistic tendency to assume that all imbalances can and must be corrected by the government. Currently, the global health crisis spurred by the COVID-19 pandemic presents the opportune moment to examine the ideological impact of socialism on disparate social and economic policy outcomes. Because of the complexity of our social contexts, it remains necessary to consult and test the validity of ideological claims before establishing them as uncontested truth. This study makes the case that socio-economic inequality can be traced to policy issues where ideological assumptions have been esteemed over empirical evidence. Using a qualitative approach, the case of South Africa will be used to assess the relationship between ideology and socio-economic policymaking by examining the effect of social justice remedies as the answer to inequality. To change economic behavior and outcomes, one must endeavor to understand the dominant thinking and belief system as promulgated by far left ideologies such as socialism. The findings indicate the centrality of redistribution as the unanimous victor able to ensure roughly equal economic outcomes for all social groups. An assumption with disastrous and even counterproductive consequences. Since ideologies are largely closed systems of thought, they conceal socio-economic realities which can only be addressed when policy preferences are revisited and re-evaluated.